Primary plasma cell leukemia: consensus definition by the International Myeloma Working Group according to peripheral blood plasma cell percentage - Fernandez De Larrea, Carlos; Kyle, Robert; Rosinol, Laura; Paiva, Bruno; Engelhardt, Monika; Usmani, Saad; Caers, Jo; Gonsalves, Wilson; Schjesvold, Fredrik; Merlini, Giampaolo; Lentzch, Suzanne; Ocio, Enrique; et al. (Blood Cancer Journal, 2021)
Primary plasma cell leukemia (PCL) has a consistently ominous prognosis, even after progress in the last decades. PCL deserves a prompt identification to start the most effective treatment for this ultra-high-risk disease. The aim of this position paper is to revisit the diagnosis of PCL according to the presence of circulating plasma cells in patients otherwise meeting diagnostic criteria of multiple myeloma. We could identify two retrospective series where the question about what number of circulating plasma cells in peripheral blood should be used for defining PCL. The presence of ≥5% circulating plasma cells in patients with MM had a similar adverse prognostic impact as the previously defined PCL. Therefore, PCL should be defined by the presence of 5% or more circulating plasma cells in peripheral blood smears in patients otherwise diagnosed with symptomatic multiple myeloma.
CRIS-Team Scopus Importer:2023-03-23